TREN BAHASA DAN IDENTITAS KOLEKTIF SANTRI DALAM PENGGUNAAN BAHASA GAUL: STUDI BAHASA “MENYALA ABANGKUH” - Sari Ani; Inayatur Rahman; Fetty Khoiriyah (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe and explain language trends in influencing social interactions and group dynamics among students and the positive or negative impacts of the use of the language trend "Menyala Abangkuh' on the social and emotional development of students. This study is a type of qualitative research that refers to descriptive descriptions. The data for this study include words or phrases used among students both online and in person. Data collection was carried out by means of observation, interviews and FGDs. Data analysis was carried out through three stages, namely, qualitative data analysis, interpretation and conclusions. The results of the study show 1) a place of expression, 2) a sense of enthusiasm and pride, 3) increasing self-confidence and solidarity, 4) strengthening a sense of togetherness, 5) increasing enthusiasm and solidarity among students, 6) the long-term potential of the phrase "Menyala Abangkuh", plays a role in preserving slang and providing long-term impacts.